A new conjugate gradient algorithm for noise reduction in signal processing and image restoration - Huang, Pan; Liu, Kaiping (Frontiers in Physics, 2022)
Noise-reduction methods are an area of intensive research in signal processing. In this article, a 4 new conjugate gradient method is proposed for noise reduction in signal processing and image 5 restoration. The superiority of this method lies in its employment of the ideas of accelerated 6 conjugate gradient methods in conjunction with a new adaptive method for choosing the step 7 size. In this work, using some assumptions, the weak convergence of the designed method was 8 established. As example applications, we implemented our method to solve signal-processing 9 and image-restoration problems. The results of our numerical simulations demonstrate the 10 effectiveness and superiority of the new approach.